Finite element modeling of a rail resting on a Winkler-Coulomb foundation and subjected to a moving concentrated load - Toscano Corrêa, R.; Pinto da Costa, A.; Simões, F.M.F. (International journal of mechanical sciences, 2018)
•A FE formulation is developed for beams on continuous frictional foundations under moving loads; the true nonsmooth character of Coulombus friction law is assumed.•A method for nonsmooth mechanical systems is adopted for the time integration.•Critical velocities, energy balances and amplification factors are determined for several intensities of the frictional parameter.•The effects of the frictional parameter on the foundations impulse and on the beams dynamic configuration are investigated.•The effects of the foundations stiffness, load velocity and beam length on the displacement and moment dynamic amplification factors are investigated. A model for the dynamic behavior of an Euler-Bernoulli beam on a frictional-elastic foundation under the action of a uniformly moving concentrated load is presented. The frictional part of the foundation’s behavior is of the Coulomb type distributed over the beam’s length and may represent the dissipative behavior due to the frictional sliding between the aggregates composing railway ballasts. Critical velocities, energy balances and dynamic amplification factors are computed based on a formulation and a numeric algorithm that take into account the nonsmooth character of friction.